2022
DOI: 10.3390/cells11152443
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA2919 Suppresses Rabbit Dermal Papilla Cell Proliferation via trans-Regulatory Actions

Abstract: Hair follicles (HFs) are complex organs that grow cyclically during mammals’ growth and development. Long non-coding RNAs (lncRNAs) cannot be translated into proteins and play crucial roles in many biological processes. In our previous study, candidate lncRNAs associated with HF cyclic regeneration were screened, and we identified that the novel lncRNA, lncRNA2919, was significantly expressed during catagen. Here, we identified that lncRNA2919 has no coding potentiality and is highly expressed in the cell nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The PrimeScript 1st Strand cDNA Synthesis Kit (Takara, Dalian, China) was used for the synthesis of high-quality rabbit skin cDNA, and then PCR was performed using Phanta Max Super-Fidelity DNA Polymerase (Vazyme, Nanjing, China). Following the steps, the overexpression vectors of pcDNA3.1-EGR1 and pcDNA3.1-DNMT1 were constructed, and pcDNA3.1-lncRNA2919 was constructed using the full-length sequence of lncRNA2919 [ 46 ]. The short hairpin RNA (shRNA)-lncRNA2919 and small interfering RNA (siRNA)-EGR1 were designed and purchased from GenePharma Co., Ltd. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…The PrimeScript 1st Strand cDNA Synthesis Kit (Takara, Dalian, China) was used for the synthesis of high-quality rabbit skin cDNA, and then PCR was performed using Phanta Max Super-Fidelity DNA Polymerase (Vazyme, Nanjing, China). Following the steps, the overexpression vectors of pcDNA3.1-EGR1 and pcDNA3.1-DNMT1 were constructed, and pcDNA3.1-lncRNA2919 was constructed using the full-length sequence of lncRNA2919 [ 46 ]. The short hairpin RNA (shRNA)-lncRNA2919 and small interfering RNA (siRNA)-EGR1 were designed and purchased from GenePharma Co., Ltd. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…The precursor miRNAs are exported from the nucleus to the cytoplasm and cleaved again by the Dicer enzyme to form miRNA double-stranded bodies containing Long noncoding RNA is a transcript that does not code for protein and is greater than 200 nucleotides in length [38]. Its sequence conservation and expression levels are lower than those of protein-coding genes, but a growing body of evidence confirms that it plays a key role in biological processes such as organ growth and development [39], cell proliferation and differentiation [40], glycolipid metabolism [41], and disease [42]. This is mainly due to the intrinsic nature of RNA molecules and their ability to form complex secondary structures that allow them to bind a wide range of molecules.…”
Section: Ncrnas and Their Mechanisms Of Actionmentioning
confidence: 99%
“…In addition, a large number of studies have also shown that these three RNAs are widely involved in various important life activities in animals, including organ growth and development, cell proliferation and differentiation, glycolipid metabolism, and disease aspects, etc. [39,[53][54][55].…”
Section: Ncrnas and Their Mechanisms Of Actionmentioning
confidence: 99%
“…Hair follicles rely on periodic cyclic growth to achieve hair growth and renewal, and their periodic changes determine the periodic growth and loss of hair, while the periodic development of hair follicles is affected by a variety of factors and is regulated by a series of signal molecules [9][10][11]. As the "material basis" of fur growth, hair follicles are not only regulated by genetic and nutritional factors but are also affected by environmental temperature and humidity [12][13][14][15]. Many studies have been conducted on animals under heat and cold stresses [16][17][18], while the effect of the seasons on fur rabbits has rarely been reported, and the mechanism of seasonal influence on hair follicle development remains unclear.…”
Section: Introductionmentioning
confidence: 99%